Counting the cost of over‐the‐counter codeine containing analgesic misuse: A retrospective review of hospital admissions over a 5 year period. (18th September 2017) - Mill, Deanna; Johnson, Jacinta L.; Cock, Victoria; Monaghan, Emily; Hotham, Elizabeth D.
Abstract: Introduction and Aims: Combination analgesics containing codeine (CACC) are currently available over‐the‐counter (OTC) in many countries following a pharmacist's advice. Published case reports detail life‐threatening morbidities associated with OTC‐CACC misuse, although the cost of treating such patients has not been quantified. This study aims to: (i) identify and detail patients admitted to an Australian tertiary teaching hospital over a 5 year period with sequelae of OTC‐CACC misuse; and (ii) estimate the costs of identified hospital admissions. Design and Methods: Using International Classification of Diseases (10th revision) diagnostic codes, a structured search was performed to identify admissions to a tertiary teaching hospital, relating to CACC misuse, over the defined period. A retrospective case note review provided data detailing patient characteristics, presenting morbidities and resultant interventions, and an approximate cost was calculated for identified admissions. Results: Ninety‐nine OTC‐CACC‐related admissions (for 30 individual patients) were identified. Most related to gastrointestinal morbidities secondary to ibuprofen/codeine misuse. Mean length of stay per admission was 5.9 days, with 10.1% of admissions requiring intensive care. Patients consumed a daily mean of 28 OTC‐CACC tablets for a mean of 606 days prior to admission. These 99 admissions were estimated to cost the health system AU$1 008 082 with a mean cost per admission of AU$10 183. Discussion and Conclusions: The outcomes of OTC‐CACC misuse are serious and come at a significant cost to patient health and the Australian health‐care system. Identification and management of this cohort appears sub‐optimal with delays in diagnosis and high readmission rates.